2021
DOI: 10.1111/1759-7714.14277
|View full text |Cite
|
Sign up to set email alerts
|

Update on adjuvant therapy in completely resected NSCLC patients

Abstract: In patients with completely resected non-small cell lung cancer (NSCLC), postoperative adjuvant chemotherapy has been associated with improvement in survival by minimizing the risk of recurrence. For years, systemic chemotherapy including platinum based regimen has been a mainstay treatment modality of adjuvant treatment after complete resection. ADAURA study showed that among completely resected IB to IIIA NSCLC, disease-free survival was significantly better in patients under adjuvant osimertinib than a plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…The results suggested that 1-year, 3-year, and 5-year OS increased in all stages, including stages I–III. In a previous study, postoperative adjuvant treatments, including chemotherapy, radiotherapy, immunotherapy and targeted therapy, were proven to be effective in operable lung cancer patients but still had limitations ( 32 ). Therefore, this also explained why there was no significant increase in 5-year OS of stages II and III patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that 1-year, 3-year, and 5-year OS increased in all stages, including stages I–III. In a previous study, postoperative adjuvant treatments, including chemotherapy, radiotherapy, immunotherapy and targeted therapy, were proven to be effective in operable lung cancer patients but still had limitations ( 32 ). Therefore, this also explained why there was no significant increase in 5-year OS of stages II and III patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) accounts for over 80% of lung cancer diagnoses ( 1 ). Heredity, environment, immunity, and bad habits (especially smoking) are common risk factors for NSCLC ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stage I–IIIA NSCLCs are considered relatively early stages, and if possible, complete resection is the treatment of choice ( 2 ). stage III NSCLC is a heterogeneous group in terms of tumor burden and distribution, and often requires a multidisciplinary team approach ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%